Quasi-synchronous code-division multiple access with high-order modulation. - Van Houtum, W.J (IEEE Transactions on communications)
Code-division multiple access (CDMA) is a multiplexing technique where a number of users simultaneously access a transmission channel by modulating and spreading their signals with preassigned codewords. This paper studies the performance of CDMA signals with orthogonal (Walsh-Hadamard) codewords and synchronization errors smaller than the chip time. Two high-order modulation techniques, M-level quadrature amplitude modulation (M-QAM) and M-level phase-shift keying (M-PSK) are compared with respect to bit-error rate (BER). The results are especially important for the return channel of cable TV networks and summarized as follows: 1) Synchronization errors between transmitters lead to interference noise, whereas synchronization errors between the transmitter and the receiver lead to a decreased amplitude of the received user signal. Both effects have significant impact on the system performance. 2) Closed expressions are obtained for the BER of a CDMA signal with M-PSK and M-QAM with a given maximum synchronization error. 3) The higher the modulation order, the more sensitive the system gets for synchronization errors. 4) The BER is highly dependent on the assigned codewords out of the Walsh-Hadamard code set. 5) The BER performance of M-QAM outperforms that of M-PSK